Health Behavior Change in Older Adults: Testing the Health Action Process Approach at the Inter‐ and Intraindividual Level. Issue 3 (12th October 2017) - Bierbauer, Walter; Inauen, Jennifer; Schaefer, Sabine; Kleemeyer, Maike Margarethe; Lüscher, Janina; König, Claudia; Tobias, Robert; Kliegel, Matthias; Ihle, Andreas; Zimmerli, Lukas; Holzer, Barbara M.; Siebenhuener, Klarissa; et al.
Abstract : Background: Health behavior change theories usually claim to be universally and individually applicable. Most research has tested behavior change theories at the interindividual level and within young‐to‐middle‐aged populations. However, associations at the interindividual level can differ substantially from associations at the intraindividual level. This study examines the applicability of the Health Action Process Approach (HAPA) at the inter‐ and the intraindividual level among older adults. Methods: Two intensive longitudinal studies examined the HAPA model covering two different health behaviors and two different time spans: Study 1 (physical activity, N = 52 × 6 monthly observations) and Study 2 (medication adherence, N = 64 × 30 daily observations). The HAPA constructs (risk awareness, outcome expectancy, self‐efficacy, intention, action planning, action control), and self‐reported behaviors were assessed. Results: Overall, at the interindividual level, results of both studies largely confirmed the associations specified by the HAPA. At the intraindividual level, results were less in line with the HAPA. Only action control emerged as consistent predictor of behavior. Conclusions: This study emphasises the importance of examining health behavior change theories at both, the inter‐ and the intraindividual level.